Teaching Essay Writing Using Authentic Materials to Improve Students' Writing Performance: Mengajar Menulis Esai Menggunakan Bahan Otentik untuk Meningkatkan Performa Menulis Siswa - El Sulukiyyah, Ana Ahsana; Aisyah, Rasyidah Nur (JEES (Journal of English Educators Society), 2019)
This study used authentic material as the tool in essay writing class. Authentic material is made not for teaching need; it is the material that bring real language knowledge. It can be brought to the class as a learning tool. There two beneficial types of authentic materials; printed and audio authentic materials. This research used authentic printed materials to improve students' writing achievement. This is a Classroom Action Research in three cycles. This study aims to explain in detail the implementation of authentic printed material in writing class and how the authentic material can improve students ' writing achievement. The result is the research has been done in three cycles, because the first and second cycle could not reach the goal. The third cycle finally could reach the criteria of success. The conclusion of this research is authentic material can improve students' writing achievement and it is recommended to use authentic material in writing class and other language classes.